Epizootiological and Epidemiological Situation in the Tularemia Natural Foci of Siberian and Far East Federal Districts in 2010 and Prognosis for 2011 - L. P. Okunev; A. V. Mazepa (Проблемы особо опасных инфекций, 2011)
Summarized data on the condition of tularemia natural foci in the territory of Siberia and Far East for 10 months of 2010 are presented in brief. Information on human morbidity during this period is given. The prognosis of epizootiological situation for 2011 is presented.